Childhood’s Portable Atlas: María Negroni’s Extraordinay Letters - Punte, María José (Meridional. Revista Chilena de Estudios Latinoamericanos, 2017)
Argentinian writer María Negroni has been working in recent years on a series of books which are simultaneously coherent and made of splitting fragments. One of the latest, Cartas extraordinarias (Extraordinary Letters) (2013), presents some challenges with respect to genre definitions. It could be read following Florencia Garramuño’s ideas and what she describes as the new forms of “no specificity” in art. The simplest definition about Negroni’s book is that it is an anthology of apocryphal letters: the author presents false letters of writers we used to read in our childhood. But that does not explain the kind of genre we are dealing with. We probably should read this book as a volume of short stories, even if it is not presented as such. But that is not the only challenge. The book works with notions such as collection and montage, anachronism and false adscriptions. Childhood is alluded through the subject but also through the form and materiality of the volume. Negroni works together, hand in hand, with the Uruguayan painter Fidel Sclavo. They reach a dialogue between image and written text, which is disconcerting and ambiguous, beautiful and nostalgic at the same time.